IMPLEMENTASI PENDIDIKAN KARAKTER SISWA KELAS V DI SDN 2 LABUAPI - Wulandari Putri, Astri; Witono, A Hari; Nisa, Khairun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research examines the implementation of character education at SDN 2 Labuapi, both inside and outside the classroom. The approach used is qualitative descriptive with the aim of describing in depth character education activities in schools. The subjects of this research were a number of class V students. Data was collected from January to April 2024 through interviews with school principals, teachers, and observations of a number of students' activities. The results of the research show that character education is applied in class V learning at SDN 2 Labuapi through the planning, learning implementation and evaluation stages. Teachers actively integrate character values ​​into lesson plans (RPP) and daily activities, giving concrete examples such as being polite and courteous towards teachers, helping friends, being disciplined, managing active classes, and instilling values. honesty and empathy. Evaluation is carried out to improve and optimize future learning processes. The results of research on character education outside the classroom show that character education at SDN 2 Labuapi is carried out in taekwondo and scout extracurricular activities. The results of implementing character education at SDN 2 Labuapi are that students carry out character education, are more disciplined and responsible for themselves both inside and outside the classroom.